1994
DOI: 10.1007/bf00004342
|View full text |Cite
|
Sign up to set email alerts
|

Osmoregulation in the stenohaline freshwater catfish, Heteropneustes fossilis (Bloch) in deionized water

Abstract: Transfer of the stenohaline catfish, Heteropneustes fossilis from tap water (TW) to deionized water (DW) resulted in an increase in the glomerular filtration rate, urine volume and osmolar and free water clearance. In a closed system, where the DW was renewed only once a day, no change in the plasma osmolality was evident for up to 14 days. When DW was renewed four times a day for 25 days, a significant reduction in the plasma osmolality was observed within 24h. When the fish were transferred back to TW, plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…These adjustments observed in fish exposed to deionized water presumably reflect the steepness of the ionic gradients and the increased energetic demand for active transepithelial NaCl absorption (Lee et al, 1996;Sakuragui et al, 2003Sakuragui et al, , 2007. Both prolactin and cortisol production are greatly stimulated in fish exposed to deionized water and the particular concentrations and ratio of these osmoregulatory hormones may provide a sensory clue for alteration of branchial epithelial ultrastructure and function in ion-poor environments (Parwez et al, 1994). The changes in fish osmoregulation that occur both at extremely low (deionized water) and strongly hyperhaline (>2× seawater) salinities suggest that unique mechanisms are involved in conferring tolerance to extreme salinities.…”
Section: −1mentioning
confidence: 99%
“…These adjustments observed in fish exposed to deionized water presumably reflect the steepness of the ionic gradients and the increased energetic demand for active transepithelial NaCl absorption (Lee et al, 1996;Sakuragui et al, 2003Sakuragui et al, , 2007. Both prolactin and cortisol production are greatly stimulated in fish exposed to deionized water and the particular concentrations and ratio of these osmoregulatory hormones may provide a sensory clue for alteration of branchial epithelial ultrastructure and function in ion-poor environments (Parwez et al, 1994). The changes in fish osmoregulation that occur both at extremely low (deionized water) and strongly hyperhaline (>2× seawater) salinities suggest that unique mechanisms are involved in conferring tolerance to extreme salinities.…”
Section: −1mentioning
confidence: 99%
“…The changes seen (Figure 1) indicated that iono/osmoregulatory homeostasis of goldfish had been perturbed and that new steady‐state conditions were achieved. The results shown in Figure 1 are consistent with previous observations in goldfish (Chasiotis et al ., 2009) as well as other fish species ( e.g ., Kolosov & Kelly, 2016; Parwez et al ., 1994) acclimated to ion‐poor conditions. While changes in salt and water balance were observed in response to diminished water ion content, no significant effect of dietary ion concentration on serum osmolality and serum chloride concentration was observed when fish were held in FW.…”
Section: Discussionmentioning
confidence: 99%
“…Ghrelin in the brain stimulates the secretion of pituitary hormones, such as PRL and GH (Kaiya et al ., 2003a,b; Unniappan & Peter, 2004). PRL, known as a freshwater‐adapting hormone, plays an important role in the ability of fishes to acclimate to a hypoosmotic environment (Parwez et al ., 1994; Sakamoto & McCormick, 2006). PRL is believed to act on osmoregulatory organs to prevent ion loss and water uptake by changing the permeability of epithelia (Manzon, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Na /K -ATPase activity profiles of teleosts at branchial and renal levels and improve hypoion regulation after transfer to different salinities (Peter et al, 2011;Arjona et al, 2011;Deal and Volkoff, 2020). Extensive research work has been carried out on the osmoregulatory, energetic, and endocrine aspects of economically important freshwater catfish, H. fossilis (Parwez et al, 1979(Parwez et al, , 1984(Parwez et al, , 1994Goswami et al, 1983;Parwez and Goswami, 1985;Sherwani and Parwez, 2000, 2008. However, the role of T during 4 osmoionic regulation in this fish remains to be elucidated.…”
mentioning
confidence: 99%